Frailty syndrome and associated factors in elderly residents in longterm institutions - Melo, Elisa Moura de Albuquerque (2018)
Descriptive study in long-term institutions to investigate the prevalence of frailty and associated factors in institutionalized elderly and its association with sociodemographicvariables and health conditions. A total of 214 elderly people, most of them females (69.6%), single marital status (53.7%), one year of schooling (54.4%) and income of up to a minimum wage (73.4%) were investigated. As to cognition, 79.4% were disapproved for significant errors. Frailty syndrome was identified in 70.1% of the elderly. All the factors included in the fragility scale reached statistical significance. In the multivariate analysis, the factors that contribute most to the fragility are: cognition, functional independence, health self-assessment, frequency of social support, perception of weight loss and depression.